Limitations to accessing legal representation in Kenya's RSD processes - Imbosa, E; Maina, A (Refugee Studies Centre, University of Oxford, 2020)
Opportunities for asylum seekers in Kenya to appeal refugee status determination (RSD) decisions are restricted by limited access to legal representation.